Pandangan Orientalis dalam Kritik Sanad dan Matan Hadis - Farid Adnir; Yudi Pranata Munthe; Juwita Elisna Rambe (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Hadith is one of the primary sources of Islamic teachings after the Qur'an. The authenticity of Hadith has been preserved through the methodologies of sanad (chain of transmission) and matan (textual content) criticism developed by Muslim scholars since the early period of Islam. However, in the development of Western Islamic studies, several Orientalist scholars have offered critical perspectives on the authenticity of Hadith. This study aims to analyze Orientalist views on sanad and matan criticism and to examine the responses of Muslim scholars to these perspectives. The research employs a library research method with a descriptive-analytical approach by reviewing relevant books, scientific journals, and academic literature. The findings reveal that Orientalists, particularly Ignaz Goldziher and Joseph Schacht, argue that many Hadiths emerged as products of social, political, and legal developments within the Muslim community after the Prophet Muhammad's era. They question the reliability of sanad, claiming that many chains of transmission were reconstructed by later generations to legitimize specific legal opinions and sectarian positions. Furthermore, Orientalist matan criticism emphasizes historical analysis to uncover the socio-historical context behind the emergence of Hadith traditions. In contrast, Muslim scholars reject many of these conclusions, arguing that Orientalists overlook the rigorous verification system and sophisticated methodologies of Hadith criticism established within the Islamic scholarly tradition. Nevertheless, Orientalist studies have contributed to enriching academic discourse on contemporary Hadith studies. Therefore, understanding Orientalist perspectives on sanad and matan criticism is essential for recognizing the methodological differences between the Islamic scholarly tradition and Western academic approaches.